2020
DOI: 10.3389/fcell.2020.618733
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interactions Between Membrane-Bound Organelles, Biomolecular Condensates and the Cytoskeleton

Abstract: Membrane-bound and membraneless organelles/biomolecular condensates ensure compartmentalization into functionally distinct units enabling proper organization of cellular processes. Membrane-bound organelles form dynamic contacts with each other to enable the exchange of molecules and to regulate organelle division and positioning in coordination with the cytoskeleton. Crosstalk between the cytoskeleton and dynamic membrane-bound organelles has more recently also been found to regulate cytoskeletal organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 232 publications
(402 reference statements)
0
21
0
Order By: Relevance
“…Overall, DCD, consisting of a secondary and irreversible intracellular calcium increase, hence the term ‘dysregulated calcium dynamics’, has been shown to enhance mitochondrial degradation which ultimately leads to energy failure due to a decreased number of mitochondria [ 321 ]. Furthermore, neuronal survival is also dependent on the balancing of mitochondrial fission and fusion, which in turn affects microtubule-mediated mobility and actin-dependent anchoring of mitochondria at presynaptic sites and dendritic shafts [ 322 , 323 ]. In specific subtypes of RGCs, it has been shown that genetic mutations of fusion proteins, such as the dynamin-like protein encoded by the OPA1 gene (OPA1 Mitochondrial Dynamin Like GTPase) gene, lead to mitochondrial fragmentation [ 324 , 325 ].…”
Section: Cellular Mechanisms Of Nmda Receptor-induced Excitotoxicity ...mentioning
confidence: 99%
“…Overall, DCD, consisting of a secondary and irreversible intracellular calcium increase, hence the term ‘dysregulated calcium dynamics’, has been shown to enhance mitochondrial degradation which ultimately leads to energy failure due to a decreased number of mitochondria [ 321 ]. Furthermore, neuronal survival is also dependent on the balancing of mitochondrial fission and fusion, which in turn affects microtubule-mediated mobility and actin-dependent anchoring of mitochondria at presynaptic sites and dendritic shafts [ 322 , 323 ]. In specific subtypes of RGCs, it has been shown that genetic mutations of fusion proteins, such as the dynamin-like protein encoded by the OPA1 gene (OPA1 Mitochondrial Dynamin Like GTPase) gene, lead to mitochondrial fragmentation [ 324 , 325 ].…”
Section: Cellular Mechanisms Of Nmda Receptor-induced Excitotoxicity ...mentioning
confidence: 99%
“…The macho-1 dissociation from dense ER during the second phase of ooplasmic segregation was another collaborative mechanism of actin and tubulin. It is well-known that both microtubules and microfilaments have a role in trafficking mRNP granules, complexes of mRNA and ribonucleoproteins (e.g., [ 30 ]). In budding yeast, it has been reported that the localization of polysome-interacting protein on the ER is regulated by microtubules [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phase-separated tau easily aggregates to form highly ordered β-sheets often associated with neurodegeneration [ 76 , 77 ]. The dynamic crosstalk between membranes and membraneless organelles highlights important features critical to the functions and maintenance of biomolecular condensates in health and disease [ 78 , 79 ].…”
Section: Atp Regulates Biomolecular Condensatesmentioning
confidence: 99%